Initial Sequencing and Characterization of the Gastrointestinal and Oral Microbiota in Urban Pakistani Adults - Batool, Maria; Ali, Syed Baqir; Jaan, Ali; Khalid, Kehkishan; Ali, Syeda Aba; Kamal, Kaynat; Raja, Afraz Ahmed; Gul, Farzana; Nasir, Arshan (Frontiers in Cellular and Infection Microbiology, 2020)
We report the initial characterization of the gastrointestinal tract (gut) and oral microbiota (bacteria) in 32 urban Pakistani adults. Study participants were between ages 18 and 40, had body mass index between 18 and 25 Kg/m2, and were students or early-career professionals. These individuals donated a total of 61 samples (32 gut and 29 oral) that were subjected to 16S ribosomal RNA (rRNA) gene sequencing. Microbiome composition of Pakistani individuals was compared against the uBiome database of selected individuals who self-reported to be in excellent health. We observed strong gender-based differences in the gut microbiome of Pakistani individuals, a skewness towards Firmicutes, and unusually high levels of Proteobacteria in the Pakistani men. These observations may indicate microbiota dysbiosis, though 16S data alone can neither establish cause nor effect to human health. Albeit conducted on a smaller scale, our report provides a first snapshot about the composition and diversity of gut and oral microbiota communities in Pakistani individuals.